Analysis of high strength composite structure developed for low-carbon-low-manganese steel sheet by laser surface treatment. (November 2021) - Syed, B.; Maurya, P; Lenka, S.; Padmanabham, G.; Shariff, SM
Highlights: High-strength layered structure was developed by applying laser surface treatment on a low C-Mn steel. Hardness improved by 150% due to formation of a mixture of hard phases. Significant improvements in both Yield Strength (40–44%) and Ultimate Tensile Strength (19–21%). Distinguishable improvements in Young's modulus. Crystallographic texture is the primary reason for improvements of Young's modulus and r-bar value. Abstract: In the present work, a high-strength composite steel structure developed by imparting laser surface hardening treatment on a low-carbon low-Manganese automotive steel sheet has been comprehensively analysed. The layered composite steel structure has been successfully developed by re-engineering the surface of the steel using diode laser hardening treatment up to a depth of 250–300 µm through its thickness. Hardness at the treated surface improved by 150% to that of its base due to formation of a mixture of hard phases constituting martensite and bainite along with retained ferrite. Indeed, coupling EBSD technique with Weibull distribution of various phase fractions determined by image quality helped analyse microstructure effectively. The tensile property of the layered composite steel sheet was found to yield significant improvements in both Yield Strength (YS) (40–44%) and Ultimate Tensile Strength (UTS) (19–21%) due to sandwich effect of composite layer constituting hardened layer and soft base accomplished by a strengthening mechanism associated with rule of mixtures concept. In fact, Young's modulus of the composite steel sheet, determined from slope of tensile stress–strain diagram was found to be convergent with ultrasonic test result. Additionally, the crystallographic texturing effects of the hardened layer and untreated base measured using standard XRD technique re-confirmed their influence on Young's Modulus and r-bar values obtained.